Uncovering the genetic mechanism of rind color trait in watermelon using fine mapping and comparative transcriptomic analysis - Liu, Sitong; Amanullah, Sikandar; An, Bohan; Guo, Yu; Liang, Xiaoxue; Liu, Xiujie; Liu, Jixiu; Gao, Yue; Zhao, Wen; Yuan, Chengzhi; Gao, Meiling (Frontiers in Plant Science, 2025)
The rind color of watermelon fruit is a significant trait that directly affects consumer acceptability. However, the genetic regulatory mechanisms underlying rind color remain poorly understood. In this study, we crossed two differentiated watermelon lines (K2Q “female parent line with a light green rind” and K2S “male parent line with a dark green rind”) and developed segregated F2 mapping populations. The dynamic development of rind color was observed by identifying the critical period for color transformation as occurring between 7 and 14 days after pollination (DAP). Genetic segregation analysis indicated that a single dominant gene regulates the major genetic locus (ClRC) associated with the dark green rind trait. Whole-genome BSA-sequencing (BSA-seq) and fine mapping analysis exposed the delimited ClRC locus to a 37.52 kb region on chromosome 08 (Chr08), comprising five genes. The pairwise sequence comparisons analysis of the parental lines revealed the single major gene (Cla97C08G161570), which encodes a 2-phytyl-1,4-β-naphthoquinone methyltransferase protein, exhibiting one non-synonymous type single nucleotide polymorphism (nsSNP) at candidate site (Chr8:27994761, C-G). The real-time quantitative polymerase chain reaction (RT-qPCR) verified the higher expression level of the K2S line on the 14 DAP than that of the K2Q line. The analysis of comparative transcriptomes (RNA-sequencing) identified a total of 940 differentially expressed genes (DEGs) associated with rind coloration in the two parental lines at three dynamic stages of development (0, 7, and 14 DAP). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis revealed key genes (C01G023430, C04G071470, C09G165830, C07G128820, C08G148460, and C08G155040) that share the same pathway as the Cla97C08G161570 gene and exhibited high levels of differential expression trend. Further, RT-qPCR verified that these genes display the same expression pattern as the Cla97C08G161570 gene, and expression levels in the dark green rind lines were significantly higher than those in the light green rind lines, suggesting the significant role in modulating the pigmentation activity.